The relationship between intelligence, adaptability, and resilience among future school counselors in wetland regions - Nina Permata Sari; Novitawati Novitawati; Muhammad Andri Setiawan (Jurnal Konseling dan Pendidikan, 2025)
School counselors are crucial in supporting student development, particularly in wetland regions where academic and social adaptation challenges are prominent. This study examined whether intelligence and adaptability significantly predict student resilience. Participants were 200 undergraduate students (aged 18–22, 2nd–6th semester) from the Guidance and Counseling Department at Lambung Mangkurat University, all residing in wetland areas. A quantitative correlational design was applied, using CFIT Scale 3 (intelligence), EPPS (adaptability), and Kraepelin Test (resilience). Analyses included Chi-Square, Pearson correlation, multiple regression, and Structural Equation Modeling (SEM). Results showed a moderate positive correlation between intelligence, adaptability, and resilience (r = 0.387, p < 0.05). Intelligence and adaptability jointly explained 42% of resilience variance (R² = 0.42). SEM confirmed good model fit (χ²/df = 2.14, RMSEA = 0.048, CFI = 0.93, TLI = 0.91). Students with high intelligence but low adaptability demonstrated weaker resilience, emphasizing adaptability as a stronger determinant than cognitive ability alone. This study is limited by its single-site sample and reliance on specific psychometric tests, restricting broader generalization. Nonetheless, findings suggest that counseling education should integrate adaptability training and resilience-building strategies to prepare future school counselors for the complex demands of wetland educational environments.